2009
DOI: 10.1128/jcm.02026-08
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Virulence Factors, and Clonality among Clinical Strains of Non-O1, Non-O139 Vibrio cholerae Isolates from Hospitalized Diarrheal Patients in Kolkata, India

Abstract: The incidence of Vibrio cholerae non-O1, non-O139 strains from hospitalized patients with acute diarrhea constituted 27.4% (n ‫؍‬ 54) of the total 197 V. cholerae strains isolated from patients in Kolkata, India, in 2003. Of 197 strains, 135 were identified as O1 serotype Ogawa and 2 were identified as O139. In the same time period, six O1 background rough strains that possessed all known virulence factors were identified. Serotype analysis of the non-O1, non-O139 strains placed 42 strains into 19 serogroups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 53 publications
5
122
2
3
Order By: Relevance
“…Several studies have reported that some Vibrio cholerae non-O1/non-O139 induce bacteremia in patients with underlying diseases, including hepatic cirrhosis and hematological disorders, which can become serious (6)(7)(8). The number of cases of Vibrio cholerae non-O1/ non-O139-induced bacterial diarrheal disease in developing countries has increased in recent years (2)(3)(4)(5). In Japan, isolation of Vibrio cholerae non-O1/non-O139 has also been reported in various regions of river water as well as fish and shellfish (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that some Vibrio cholerae non-O1/non-O139 induce bacteremia in patients with underlying diseases, including hepatic cirrhosis and hematological disorders, which can become serious (6)(7)(8). The number of cases of Vibrio cholerae non-O1/ non-O139-induced bacterial diarrheal disease in developing countries has increased in recent years (2)(3)(4)(5). In Japan, isolation of Vibrio cholerae non-O1/non-O139 has also been reported in various regions of river water as well as fish and shellfish (5).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some patients with the same severe diarrhea as that caused by Vibrio cholerae O1 and O139 have been reported, which suggests the presence of intestinal virulence factors other than the cholera toxin (3,8). We herein present a case in which an immunocompromised patient with myelodysplastic syndrome (MDS) who received azacitidine developed Vibrio cholerae non-O1/non-O139-induced bacterial diarrheal disease that resulted in a fatal outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar role for V. cholerae non-O1/non-O139 strains was identified in a large-scale molecular analysis of strains isolated during a cholera outbreak in Kolkata, India. 44 Interestingly, before the Haiti outbreak of cholera, the public health risk of human pathogens in surface waters of Haiti had not been evaluated and no reportable waterborne diseases were listed. 45 Our recent collaboration with the United States CDC reported V. cholerae non-O1/O139, Vibrio parahaemolyticus, human pathogenic viruses, and Cryptosporidium spp.…”
Section: Cholera In Haitimentioning
confidence: 99%
“…Although more than 200 O serogroups of V. cholerae have been identified so far, only O1 (El Tor and classical biotypes) and O139 are responsible for cholera epidemics (2). Serogroups other than O1 and O139 (non-O1/non-O139) are associated with sporadic cases of diarrhea (3). A variant of V. cholerae O1 El Tor biotype, possessing some attributes of the classical biotype, has emerged recently and was isolated from hospitalized patients with diarrhea more severe than that caused by typical El Tor strains (4,5).…”
Section: Introductionmentioning
confidence: 99%